MACROECONOMIC ASPECTS OF THE DEVELOPMENT OF BANK LENDING TO INDUSTRIAL ENTERPRISES: CHALLENGES OF TODAY - Alina Herasymenko (Izdevnieciba "Baltija Publishing", 2022)
The aim of the article is to highlight the key modern macroeconomic aspects and trends in the development of bank lending to industrial enterprises in highly developed countries of the world and to identify promising areas for its further development. The methodological basis of the study is the generalization of the results of applied research in the field of economics, scientific papers, statistical data, which highlight certain aspects of the development of the modern globalized economy, in particular its impact on the macroeconomic features of industrial development and bank lending to industrial enterprises. Results. The influence of financialization on the macroeconomic environment and the development of bank lending to industrial enterprises (on the example of the USA, Great Britain, Germany) is investigated. The influence of such unprecedented for the XXI century force majeure factors as the COVID-19 pandemic and the war in Ukraine on the macroeconomic environment and the development of bank lending to industrial enterprises is considered. The key trends in global economic development that stimulate transformations and structural changes in the macroeconomic environment of highly developed countries are highlighted. The role of bank lending to industrial enterprises in these processes is determined, which consists in lending to industrial innovations, as well as in the development of such promising areas as the "green" and "blue" economy. Practical implications. The practical results can be the basis for further research: on solving the problems of convergence of the financial and real sectors of the financialized economy, in particular with the participation of bank lending to industrial enterprises; on the role and importance of bank lending to industrial enterprises in overcoming the current macroeconomic consequences of the war in Ukraine; on certain aspects of the integration of bank capital into the development of industrial enterprises that are part of the "green", "blue" economy. Value/originality. The results of the study provide a deeper understanding of the role and contribution of bank lending to industrial enterprises in the processes of ensuring positive macroeconomic dynamics and maintaining macroeconomic stability, as well as allow to assess the depth of prospects for the development of bank lending to industrial enterprises.